IMPLEMENTATION OF THE RESPONSIBILITY TO PROTECT IN THE SETTLEMENT OF HUMANITARIAN CRISIS IN THE CENTRAL AFRICAN REPUBLIC BY THE UNITED NATIONS - Parulian Yusuf S. (Faculty of Law Universitas Lampung, 2019)
State’s sovereignty enables the execution of governance arrangements and state’s (primary) obligation to protect citizens from the threats of genocide, crimes against humanity, war crimes and aggression. Moreover, sovereignty is considered as a state-owned right to reject forms of interventions. The opposition that arises between sovereignty and the protection of humanity encourages the birth of Responsibility to Protect. The humanitarian crisis occurred in the Central African Republic when the Central African Republic government was unable to stop the insurgency arising in its territory. Seleka and Anti-Balaka rebels were involved in the civil war in the Central African Republic. Seleka rebels attacked a predominantly Christian and Anti-Balaka population attacking a Muslim minority. This is of concern to the international community and encourages the United Nations Security Council to take action to resolve the humanitarian crisis in the Central African Republic under Responsibility to Protect.